Patient Outcome through Collaborative Practice in Interprofessional Education: Views of the Major Stakeholders’ in Bangladesh (Bangladesh Journal of Medical Education, 2024)
Background: Interprofessional collaborative practice is required to deliver the highest quality of care for a better patient outcome. Interprofessional education (IPE) builds the foundation for collaborative practice. In this study, the views of the major stakeholders in Bangladesh were explored regarding possible patient outcomes through collaborative practice, which is promoted by interprofessional education.Methods: This descriptive cross-sectional study was carried out in seven medical colleges, three nursing institutes, one health technology institute, several hospitals, and health complexes from July 2022 to June 2023. A semi-structured self-administered questionnaire was used to conveniently collect information from 273 intern doctors, 51 recently graduated doctors, 153 nursing students, 71 senior nurses, and 104 health technicians.Results: The study showed that the means of agreement of their views on different issues related to the patient outcome through collaborative practice were within 75.6% to 86.8%. Although majority of the respondents were convinced about the patient outcome benefits of collaborative practice, the means of agreement of the intern doctors were statistically significantly lower than means of agreement of other groups in different variables.  Conclusions: Results of this study showed that the majority of the respondents acknowledged that better patient outcomes are possible through collaborative practice, which could be promoted by IPE sessions during their academic years. From this study, it is recommended that IPE should be introduced for further improvement of health service delivery, patient satisfaction, and cost effectiveness.BJME, Volume-15, Issue-01, January 2024: 25-35